Implementasi Kabijakan Corporate Social Responsibility (CSR) Pada Bidang Pendidikan Di Kabupaten Karawang - Gina Mutia Rahayu; Cusu Sugiarti; Haura Atthahara (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study discusses the Implementation of Corporate Social Responsibility (CSR) Policy in the Education Sector in Karawang Regency. The purpose of this study was to find out how the implementation of Corporate Social Responsibility (CSR) policies in the field of education in Karawang regency. Problems in the field of education are one of the priority areas in the framework of sustainable development, as a basis for improving the quality of life of the community. Thus, the Karawang Regency Government wants the implementation of CSR activities in Karawang Regency which prioritizes this field. Besides that, implementing CSR in the field of education can assist the government in improving educational facilities and infrastructure, and provide assistance to the community in improving the quality of human resources (HR) so that they are able to compete as well as benefits for companies in improving corporate image and getting good partners. according to the needs of the company itself. This study used descriptive qualitative method. Data collection techniques used literature and field studies, which consisted of observation, interviews, documentation, and mix/triangulation. Data Analysis Techniques Using interactive model analysis using the theory of Policy Implementation according to Grindle is influenced by two major variables, namely: 1) Content of Policy, including (To what extent is the interest of the target group in the content of the policy, Types of benefits received by target group, the extent to which changes are desired from a policy, whether the location of a program is appropriate, whether a policy has stated its implementation in detail, and whether a program is supported by adequate resources). 2) Implementation Environment, including (How much power, interests, and strategies are owned by the actors involved in implementing the policy, the characteristics of the institutions and regimes in power, as well as the level of compliance and responsiveness of the target group). The results showed that the Implementation of Corporate Social Responsibility (CSR) Policy Implementation in the Education Sector in Karawang Regency in general has been going well, it's just that there are still some obstacles that hinder the process of distributing CSR funds in the education sector.